Model of Policy Network in Advocacy for the Formulation of Qanun Draft on Protection and Fulfillment of the Rights of People with Disabilities - Hafni, Nur; ., Mursyidin; Riski, Aflia; Rachim, Abd.; Harliansyah, Teguh; Fatmsari, Desy (Journal of Ecohumanism, 2024)
This study aims to analyze the interaction and interdependence of policy networks, identify inhibiting and supporting factors, and formulate an effective policy network model in the formulation of the Qanun for the protection and fulfillment of the rights of persons with disabilities in North Aceh Regency. A qualitative approach was used in this study, with data collection methods including in-depth interviews, focus group discussions (FGD), observations, and document studies.The results of the study indicate that the interaction and interdependence among actors in the policy network in North Aceh Regency are still not optimal. The involved actors often work separately without adequate coordination, and differences in interests and priorities hinder the achievement of common goals. The main inhibiting factors include a lack of resources, differences in interests among actors, and low public awareness of the rights of persons with disabilities. On the other hand, supporting factors include the commitment of the local government, support from NGOs, and initiatives from the community of persons with disabilities.An effective policy network model includes enhancing coordination among actors, establishing regular communication forums, strengthening the capacity of involved actors, and active participation from the community of persons with disabilities. By implementing this model, it is expected that the formulation of the Qanun for the protection and fulfillment of the rights of persons with disabilities in North Aceh Regency can proceed more effectively and inclusively.